PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN PENGEMBANGAN SIKAP TOLERANSI DENGAN STRATEGI CYBERGOGY - Gita Amilia Rachmawati; Hasan Subekti (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This research aimed to determine the effect of cybergogy strategies implemented in blended learning to improve critical thinking ability and to develop students' tolerance attitude. This research used a one group pretest-posttest design and quantitative descriptive. The subject in this research were 16 students of VIII-I class in Junior High School 5 Gresik. The instruments in this research were test sheets and questionnaires. Data were collected by (1) pretest and posttest of critical thinking ability (2) questionnaire of students' tolerance attitude. The research results showed that there were improvements in students' critical thinking ability with a N-Gain score in medium category, and students' tolerance attitude has obtained a very tolerant category. The students gave a positive response in learning implementation. The conclusion of this research was that the cybergogy strategies could improve the students' critical thinking ability and develop to students' tolerance attitude.